Mutational and Phylogenetic Analyses of SARS-Cov-2: Bangladesh Perspective (Bangladesh Pharmaceutical Journal, 2023)
Severe acute respiratory syndrome or SARS-Cov-2 is a global pandemic causing over 6.5 million deaths worldwide. As a part of the global village, Bangladesh is also heavily affected with more than 29,000 deaths in those two years of pandemic. Though the severity and mortality rate are not so high compared to the other countries, Bangladesh also faced many difficulties combating the mutated and newer types of the Covid-19. The evolution and phylogenetic study of the virus is one of those key areas to focus in order to understand the nature of virus, its mutation pattern and gene prediction. This study investigates the evolutionary links among the older and newly emerged SARS‐Cov‐2 variants. In this study, the entire genome sequences of SARS‐Cov‐2 variants were obtained, aligned using muscle alignment, pairwise comparison was computed, differences, gaps and mutations were noted. The phylogenetics of different types of covid-19 variants were determined using a variety of evolutionary substitution models. The ultrametric and metric clustering methods, such as UPGMA and neighbor‐joining (NJ), using nucleotide substitution models allowed the inclusion of nucleotide transitions and transversions as Kimura 80 models. The findings revealed that Omicron variant forms a new monophyletic clade that is distant from other SARS‐Cov‐2 variants but surprisingly in proximity to the alpha variant, which was actually dominant in the early stage of pandemic. This finding also indicates that the omicron variant might have been there for a while, hiding the virulence and later becomes the variant of concern in the latest wave of the pandemic. This may pave the way for new researchers to find proper insight of different variants of Bangladesh in treatment plan and vaccine designing.Bangladesh Pharmaceutical Journal 26(2): 204-211, 2023 (July)